Social Isolation Is Associated With Rapid Kidney Function Decline and the Development of Chronic Kidney Diseases in Middle-Aged and Elderly Adults: Findings From the China Health and Retirement Longitudinal Study (CHARLS) - Zhou, Weiran; Li, Yang; Ning, Yichun; Gong, Shaomin; Song, Nana; Zhu, Bowen; Wang, Jialin; Zhao, Shuan; Shi, Yiqin; Ding, Xiaoqiang (Frontiers in Medicine, 2021)
Background: There is limited evidence on the relationship between social isolation and renal outcomes. To address this gap, this study estimated the prospective relationship of social isolation with rapid kidney function decline and the development of chronic kidney disease (CKD) in middle-aged and elderly Chinese with normal kidney function. Methods: We analyzed data from 3,031 participants aged ≥ 45 years with baseline estimated glomerular filtration rates (eGFR) ≥ 60 ml/min/1.73 m2. All data were obtained from the 2011 and 2015 waves of the Chinese Longitudinal Study of Health and Retirement (CHARLS). eGFR was estimated based on a combination of serum creatinine and cystatin C. The primary outcome was rapid decline in renal function, as defined by an eGFR decrease of > 5 ml/min/1.73 m2 per year, while the secondary outcome was the development of CKD, as defined by an eGFR decrease to a level < 60 ml/min/1.73 m2. Results: During the follow-up of 4 years, 258 (8.5%) participants experienced a rapid decline in renal function, while 87 (2.9%) developed CKD. In the fully adjusted model, high social isolation was significantly related to an increased risk of experiencing a rapid decline in renal function (OR 1.805, 95% CI 1.310–2.487) and CKD onset (OR 1.842, 95% CI 1.084–3.129). Among the five components of social isolation, being unmarried, not participating in social activities, and living alone independently predicted declined renal function. Conclusions: Social isolation is significantly associated with the risk of rapid eGFR decline and CKD onset in middle-aged and older adults with normal kidney function in China.